Academic supervision to improve madrasah teacher performance - Waska Warta; Cucu Maspikah; Pepen Supendi; Yasyfi Afazani (Sean Institute, 2024)
This research aims to determine the planning for the implementation and evaluation of the academic supervision program at MTs Muhammadiyah Tarogong Kidul Garut. The method used is a qualitative method with a descriptive design, while data collection techniques consist of observation, interviews, document analysis and field notes. The informants in this research were the head of the madrasa, the deputy head of the school for curriculum and teachers at MTs Muhammadiyah Tarogong Kidul Garut. The results of the research found that 1) the head of the madrasah carries out supervision once a month and the implementation is carried out in stages, firstly holding a deliberation, secondly checking the completeness of the learning equipment, thirdly a class visit, and finally follow-up or evaluation after the supervision is carried out, 2) the implementation of supervision uses the visit technique class, 3) the evaluation carried out by the madrasah principal to improve teacher performance is through learning assessment by monitoring student exam results and it is hoped that through this evaluation teachers will further improve their performance.